Government Transparency Model in Procurement of Goods and Services in Luwu Regency - Raehana Rahman (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
Government procurement of goods and services is a sector that is highly vulnerable to irregularities and corruption practices, therefore, the implementation of transparency is a crucial aspect in realizing good governance. In Luwu Regency, although procurement has been implemented through the e-procurement system (LPSE), transparency still faces various weaknesses in public information access, process accountability, and stakeholder engagement. This study aims to analyze the government transparency model in procurement of goods and services in Luwu Regency and formulate a transparency strengthening model relevant to the regional context. The study used a qualitative descriptive approach with a case study design. Informants were determined using purposive sampling consisting of procurement officials, APIP, goods/services providers, and community elements. Data collection techniques included interviews, observations, document reviews, and literature studies on procurement regulations and transparency theory. Data analysis used the interactive model of Miles, Huberman, and Saldana. The results of the study indicate that the implementation of transparency in procurement is not optimal in four dimensions of Porumbescu (2022): organizational actors , technology , management interventions , and stakeholder environment . The main obstacles lie in limited open information, ineffective utilization of the LPSE system, weak oversight mechanisms, and a lack of public participation. This study recommends an integrative transparency model that focuses on strengthening information digitization, increasing procurement human resource capacity, collaboration-based oversight, and community involvement in procurement oversight to support public accountability in Luwu Regency.